Higher levels of concern about dieting and moderate-intensity physical activity predict orthorexia nervosa among young adults - S. Pardini; J. Szubert; C. Novara; A. Brytek-Matera (European Psychiatry, 2022)
Introduction In some individuals, interest in healthy attitudes and behaviours towards food may show obsessive signs. Preoccupation with ‘healthful’ eating may contribute to orthorexia nervosa (ON) – a strong preoccupation with “healthy eating” manifested by the avoidance of all foods considered by the individual to be “unhealthy”.